PENGARUH PENERAPAN MODEL PROBLEM BASED LEARNING MENGGUNAKAN MEDIA VIDEO ANIMASI DAN MEDIA GAMBAR BERSERI TERHADAP HASIL BELAJAR SISWA SUBTEMA LINGKUNGAN DAN MANFAATNYA - Firza Fauziah; Dadang Kurnia; Resyi A. Gani A. Gani (STKIP Subang, 2024)
Student involvement takes part and being active in the learning process in the application of the learning model is not appropriate and the vagueness of teaching materials delivered in textbooks is an intermediary medium. The purpose of this study is to improve learning outcomes on the effect of the application of the Problem-Based Learning (PBL) learning model on animated video media and serial images. The methodology in the study used a quasi-experimental method approach, population design of grade V-A and V-B students at Tunas Mekar's State Elementary School. Based on the N-Gain value of experimental class group 2 (PBL using serial image media) which is 65 higher than the average N-Gain score of experimental class group 1 (PBL using animated video media) which is 62. After the t-test, the average N-Gain value of the two groups, namely experimental class group 1 and experimental class group 2, was calculated (2.74147) > t-table (2.01537), and hypothesis testing was carried out and the hypothesis test obtained that the null hypothesis (H0) was rejected and the alternative hypothesis (Ha) was accepted. The results showed that the PBL learning model using serial image media could improve the learning outcomes of grade V students of SDN Tunas Mekar. Thus, it is concluded that the PBL model using serial image media has a higher influence than the PBL model using animated video media on improving the learning outcomes of students in grade V at SD Negeri Tunas Mekar, Bogor Regency in the odd semester of the 2023/2024 academic year.